Increased moisture content in children’s atopic skin. - Martinsen, Ø.G.; Grimnes, S.; Kirkhus, T.; Mørkrid, L.; Aas, K. (European Journal of Pediatric Dermatology, 2007)
Skin hydration measurements were carried out on 20 school children, 9 of which suffered from atopic dermatitis. Skin hydration was assessed by means of low frequency electrical susceptance measurements. Non eczematous atopic skin was found to be more hydrated than normal skin and skin hydration was furthermore found to be dependent on environmental relative humidity.